Use of hyperthermal heating and intraoperatively administered applicator for the treatment of local malignant tumors - Vasilchenko, Ilya; Braginsky, Vladimir; Rynk, Vitaly; Osintsev, Aleksey (Archive of Oncology, 2022)
Background: This article describes a method for non-contact local hyperthermal heating of patient’s tissue using inductive electromagnetic radiation. Aim: The aim of the study was a theoretical and experimental assessment of the thermal and electromagnetic parameters of the proposed method based on heating of intraoperatively administered, personal, tissue-replacing applicator using induction magnetic field. Methods: Theoretical estimates of the thermal and electromagnetic parameters of this method were performed based on heat conduction equations. An experimental study of the process was carried out using originally designed laboratory inverter and confirmed theoretical calculations. Results: The performed assessments and calculations confirmed the possibility of creating clinically effective hyperthermia in the removed tumor bed by the method of local non-contact intraoperative hyperthermia. Conclusion: The proposed method can be used both independently and in combination with chemo- and radiotherapy, thus reducing the risk of recurrence for locally advanced forms of malignant tumors of the oropharyngeal region after surgical treatment.